2019
DOI: 10.1024/0301-1526/a000743
|View full text |Cite
|
Sign up to set email alerts
|

Vascular trauma of the hand – a systematic review

Abstract: Abstract. Hypothenar or thenar hammer syndrome (HHS) and hand-arm vibration syndrome (HAVS) are diseases caused by acute or chronic trauma to the upper extremities. Since both diseases are generally related to occupation and are recognised as occupational diseases in most countries, vascular physicians need to be able to distinguish between the two entities and differentiate them from other diagnoses. A total of 867 articles were identified as part of an Internet search on PubMed and in non-listed occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Nevertheless, large prospective or comparative studies investigating endovascular, surgical and conservative treatment options in HHS are yet missing. Wahl et al ( 34 ) investigated in a systematic review of vascular traumatic disorders different therapeutic approaches and reported a pronounced inconsistency of data regarding those treatment options. However, those data included cases of HHS, thenar hammer syndrome and of hand-arm vibration syndrome while this systematic review included only patients with HHS.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, large prospective or comparative studies investigating endovascular, surgical and conservative treatment options in HHS are yet missing. Wahl et al ( 34 ) investigated in a systematic review of vascular traumatic disorders different therapeutic approaches and reported a pronounced inconsistency of data regarding those treatment options. However, those data included cases of HHS, thenar hammer syndrome and of hand-arm vibration syndrome while this systematic review included only patients with HHS.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral emboli affect the upper extremities in up to 20% of cases, 70% of which are cardioembolic while 30% are caused by vascular lesions (proximal aneurysm, traumatic lesion, etc.) [28]. Therefore, imaging of the arteries of the entire upper limb is necessary in the event of suspected embolism due to lesions of the large vessels.…”
Section: Peripheral Embolismmentioning
confidence: 99%
“…Elite athletes are exposed to the possibility of a variety of injuries and although musculoskeletal lesions are the most common cause of complain [1], some of the most devious and disabling could be vascular injuries [2,3]. The causes of venous or arterial injuries in athletes could be high-speed collisions and repetitive motions.…”
Section: Introductionmentioning
confidence: 99%